Effect of enrichment of organic selenium, inorganic selenium and vitamin E in quail ration on the performances and potency of quail egg as a source of antioxidant - Akil, Syahrir; Piliang, Wiranda Gentini; Hanny Wijaya, C.; Utomo, Desianto Budi; Wiryawan, I Komang Gede (Indonesian Animal Sciences Society, 2009)
The change of life style influences human health and it contributes to many human diseases outbreak, therefore nutrition of antioxidant is required. This study was aimed to get an optimum level of combined organic selenium, inorganic selenium and vitamin E in obtaining the best production and reproduction of quails and the highest antioxidant level in quail eggs. This study was conducted from January to August 2008.Â Numbers of observed quails were 720 individuals (360 female and 360 male quails). The treatments were applied when the quails were six weeks old. Nine treatment diets were: To (commercial diet), T1 (0.46 ppm inorganic Se + 43.50 ppm vitamin E), T2 (0.46 ppm inorganic Se + 87.00 ppm vitamin E), T3 (0.92 ppm inorganic Se + 43.50 ppm vitamin E), T4 (0.92 ppm inorganic Se +87.00 ppm vitamin E), T5 (0.46 ppm organic Se + 43.50 ppm vitamin E), T6 (0.46 ppm organic Se + 87.00 ppm vitamin E), T7 (0.92 ppm organic Se + 43.50 vitamin E) and T8 (0.92 ppm organic Se 0.92 + 87.00 ppm vitamin E). The design of the experimental applied was a factorial â nested design. Any significant differences among the treatment diets were analysed using Duncans test. The result of this study indicated that treatment T7 (0.92 ppm organic selenium + 43.50 ppm vitamin E) in general gave the highest content of selenium in meat, in egg albumin, egg yolk, vitamin E in egg yolk, glutathione peroxidase (GSH-Px), activity of antioxidant, hatchability and low mortality. Key Words: Quail, Selenium, Vitamin E, Antioxidant